Decoding the mannitol enigma in filamentous fungi - Solomon, P.; Waters, O.; Oliver, Richard (Elsevier Ltd, 2007)
Mannitol is a 6-carbon polyol that is among the most abundant biochemical compounds in the biosphere. Mannitol has been ascribed a multitude of roles in filamentous fungi including carbohydrate storage, reservoir of reducing power, stress tolerance and spore dislodgement and/or dispersal. The advancement of genetic manipulation techniques in filamentous fungi has rapidly accelerated our understanding of the roles and metabolism of mannitol. The targeted deletion of genes encoding proteins of mannitol metabolism in several fungi, including phytopathogens, has proven that the metabolism of mannitol does not exist as a cycle and that many of the postulated roles are unsupported. These recent studies have provided a much needed focus on this mysterious metabolite and make this a fitting time to review the roles and metabolism of mannitol in filamentous fungi.